Pencegahan Stunting, Wujudkan Generasi Emas Indonesia Berkualitas - Arifin, Zainul; Sa’adah, Lailatus; Erawati, Sherly Hesti; Sugiono, Djoko (Jurnal ABM Mengabdi, 2024)
This community service activity aims to provide knowledge and awareness about how important it is to prevent stunting, because stunting is a serious problem that affects the growth and development of children due to malnutrition (PE / micronutrients) of pregnant women, which has an impact on fetal growth, Infants before and early birth, and is an indicator of chronic nutritional status that describes the disruption of overall socioeconomic conditions in the past, especially in the first 2 (two) years of a child's life whose impact is difficult to correct. Service activities are carried out through socialization, counseling, mentoring, and concrete actions. Service activities are carried out through socialization, counseling, mentoring, and concrete actions. The participation of Lazis Sabilillah's assisted mothers is very good and contributes actively in providing advice and direction related to the implementation of activities. The impact of this mentoring activity is expected to help reduce stunting rates, especially in Blimbing Village and Malang City in general, besides that it is expected to increase local community knowledge on how to prevent stunting. This activity is a breakthrough from Lazis Sabilillah to proactively support government programs in stunting prevention in Indonesia